Thermoanalytical investigation of valsartan binary eutectic forming systems and low transition temperature mixtures (LTTM) - Ferreira, Patricia O. [UNESP]; Ferreira, Laura T. [UNESP]; Almeida, Amanda C. [UNESP]; Meneguin, Andréia B. [UNESP]; Chorilli, Marlus [UNESP]; Eusébio, M. Ermelinda S.; Castro, Ricardo A.E.; Caires, Flávio J. [UNESP] (Elsevier, 2025)
In this work, binary mixtures of valsartan and menthol (MENT), thymol (THY) and catechol (CAT) were investigated using thermal analysis, complemented by powder X-ray diffraction and infrared spectroscopy. Eutectic forming systems were obtained for samples prepared by neat mechanochemistry using crystalline valsartan (VALc), whose thermal behavior deviates considerably from the ideal prediction. For VALc-CAT, the eutectic temperature is about 40 °C lower than predicted by Schröeder-van Laar equation, although the eutectic mixture is not liquid under ambient conditions. After cooling from the melt, the samples give rise to amorphous phases. Attending to their glass transition temperature, mixtures were selected (xVAL = 0.3 for VAL-MENT and VAL-THY, xVAL = 0.5 for VAL-CAT) that are liquid under ambient conditions (Low Transition Temperature Mixtures, LTTM) or at physiological temperature. Amorphous phases were also obtained for the same composition, for VAL-MENT and VAL-THY by neat grinding using amorphous valsartan (VALa). The release profiles of valsartan through a cellulose dialysis membrane into a pH 6.8 phosphate buffer at 37 °C were evaluated for VAL-MENT and VAL-THY (xVAL = 0.3) that are liquid at room temperature and VAL-CAT (xVAL= 0.5) that is liquid at physiological temperature) and compared with that of pure VALa.